2013
DOI: 10.1093/ejcts/ezt070
|View full text |Cite
|
Sign up to set email alerts
|

Remote access perfusion for minimally invasive cardiac surgery: to clamp or to inflate?

Abstract: RAP can be successfully and safely implemented in minimally invasive cardiac surgery. EBO and transthoracic clamping of the ascending aorta are performing equally in terms of feasibility and procedural success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Several smaller reports have demonstrated the safety of the endoaortic balloon [16,[22][23][24]. Our large experience corroborates these findings.…”
Section: Commentsupporting
confidence: 87%
“…Several smaller reports have demonstrated the safety of the endoaortic balloon [16,[22][23][24]. Our large experience corroborates these findings.…”
Section: Commentsupporting
confidence: 87%
“…Loforte et al [7] also found the same CPB-time and X-time in their comparison study between EAB and EAC in MIMVS approach. Krapf et al [8] reported shorter CPB-and X-times in the EAB group in their comparison study in two large groups. However, these groups contained not only MV surgery patients but also endoscopic bypass surgery and other procedures.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies, with relatively small groups, showed that EAC compared with EAB performs equally in terms of safety and the low risk of morbidity and mortality. These studies describe a longer procedure time, CPB time and cross-clamp (CX)-time when the EAB-technique is compared with EAC-technique [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Krapf et al, reported equal performances of endoaortic balloon occlusion and aortic transthoracic clamping in terms of feasibility and procedural success. [13] CS cannulation Patency and diameter of CS is best visualized during TEE by starting from the high four-chamber view. The probe is then advanced until the CS is seen entering the RA adjacent to the tricuspid annulus.…”
Section: Arterial Cannulationmentioning
confidence: 99%